2014
DOI: 10.1007/s10393-013-0898-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Mycobacterium ulcerans and Aquatic Plant Communities of West Africa: Implications for Buruli Ulcer Disease

Abstract: Numerous studies have associated Buruli ulcer (BU) disease with disturbed aquatic habitats; however, the natural reservoir, distribution, and transmission of the pathogen, Mycobacterium ulcerans, remain unknown. To better understand the role of aquatic plants in the ecology of this disease, a large-scale survey was conducted in waterbodies of variable flow throughout three regions of Ghana, Africa. Our objectives were to characterize plant communities and identify potential relationships with M. ulcerans and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 41 publications
3
31
0
2
Order By: Relevance
“…These 5 Orders may not be the primary habitat of M. ulcerans in the wild, as the full biotic extent of M. ulcerans distribution is still unknown, but they are commonly found to be persistently infected and appear to be important hosts [32]. Previous work has found that M. ulcerans abundance does respond to water body type, being more commonly detected in swamps (still lentic systems) than rivers (flowing lotic systems) in Ghana [33], [34]. The pathogen is associated with lowland, flat, swampy areas in contact with stagnant water [35], is known to have complex seasonal dynamics [32], and appears to be present at low levels throughout the entire local biotic community along the year [29].…”
Section: Introductionmentioning
confidence: 99%
“…These 5 Orders may not be the primary habitat of M. ulcerans in the wild, as the full biotic extent of M. ulcerans distribution is still unknown, but they are commonly found to be persistently infected and appear to be important hosts [32]. Previous work has found that M. ulcerans abundance does respond to water body type, being more commonly detected in swamps (still lentic systems) than rivers (flowing lotic systems) in Ghana [33], [34]. The pathogen is associated with lowland, flat, swampy areas in contact with stagnant water [35], is known to have complex seasonal dynamics [32], and appears to be present at low levels throughout the entire local biotic community along the year [29].…”
Section: Introductionmentioning
confidence: 99%
“…PCR was carried out using methods described by McIntosh et al (2014) [26], Williamson et al (2008) [19], and Williamson et al (2014) [39] where all samples were initially subjected to amplification of IS 2404 . Positive samples were further assayed for the presence of the enoyl reductase (ER) domain encoded on the plasmid responsible for mycolactone production, as previously described [19, 26, 3941]. Samples found to be ER positive were profiled when possible using variable number tandem repeat profile targeting a number of loci [19, 26, 39].…”
Section: Methodsmentioning
confidence: 99%
“…Positive samples were further assayed for the presence of the enoyl reductase (ER) domain encoded on the plasmid responsible for mycolactone production, as previously described [19, 26, 3941]. Samples found to be ER positive were profiled when possible using variable number tandem repeat profile targeting a number of loci [19, 26, 39]. Standard operating procedures for quality assurance of molecular analyses were strictly followed according to the Quality Assurance/Quality Control Guidance for Laboratories performing PCR analyses on Environmental Samples and microbial source tracking by the Environmental Protection Agency, USA [42].…”
Section: Methodsmentioning
confidence: 99%
“…Still others have found that direct contact with aquatic environments is a major risk factor (Aiga et al, 2004;Raghunathan et al, 2005;Debacker et al, 2006;Sopoh et al, 2010), and M. ulcerans has been detected in fish (Eddyani et al, 2004), aquatic snails (Marsollier et al, 2004), aquatic insects (Portaels et al, 1999), and submerged terrestrial plants (McIntosh et al, 2014). While the culturing of M. ulcerans from an aquatic invertebrate (Portaels et al, 2008) suggested a potential reservoir or vector for BU (e.g., Merritt et al, 2010), Benbow et al (2008) discounted predatory aquatic insects as a potential vector because the number of insects and presence of M. ulcerans in these insects are similar at BU-endemic and non-endemic sites.…”
Section: Introductionmentioning
confidence: 99%